Prognostic significance of visit-to-visit variability, maximum systolic blood pressure, and episodic hypertension - Rothwell, Peter M; Howard, Sally C; Dolan, Eamon; O'Brien, Eoin; Dobson, Joanna E; Dahlöf, Bjorn; Sever, Peter S; Poulter, Neil R (The Lancet (British edition), 2010)
The mechanisms by which hypertension causes vascular events are unclear. Guidelines for diagnosis and treatment focus only on underlying mean blood pressure. We aimed to reliably establish the prognostic significance of visit-to-visit variability in blood pressure, maximum blood pressure reached, untreated episodic hypertension, and residual variability in treated patients. We determined the risk of stroke in relation to visit-to-visit variability in blood pressure (expressed as standard deviation [SD] and parameters independent of mean blood pressure) and maximum blood pressure in patients with previous transient ischaemic attack (TIA; UK-TIA trial and three validation cohorts) and in patients with treated hypertension (Anglo-Scandinavian Cardiac Outcomes Trial Blood Pressure Lowering Arm [ASCOT-BPLA]). In ASCOT-BPLA, 24-h ambulatory blood-pressure monitoring (ABPM) was also studied. In each TIA cohort, visit-to-visit variability in systolic blood pressure (SBP) was a strong predictor of subsequent stroke (eg, top-decile hazard ratio [HR] for SD SBP over seven visits in UK-TIA trial: 6·22, 95% CI 4·16–9·29, p<0·0001), independent of mean SBP, but dependent on precision of measurement (top-decile HR over ten visits: 12·08, 7·40–19·72, p<0·0001). Maximum SBP reached was also a strong predictor of stroke (HR for top-decile over seven visits: 15·01, 6·56–34·38, p<0·0001, after adjustment for mean SBP). In ASCOT-BPLA, residual visit-to-visit variability in SBP on treatment was also a strong predictor of stroke and coronary events (eg, top-decile HR for stroke: 3·25, 2·32–4·54, p<0·0001), independent of mean SBP in clinic or on ABPM. Variability on ABPM was a weaker predictor, but all measures of variability were most predictive in younger patients and at lower (<median) values of mean SBP in every cohort. Visit-to-visit variability in SBP and maximum SBP are strong predictors of stroke, independent of mean SBP. Increased residual variability in SBP in patients with treated hypertension is associated with a high risk of vascular events. None.